(3OhQ GdEQTGO GdRQGYj aj GdJhYjI HCfeGW GdJYGbH GdeMUhdj GdeKdj HeMGaXI GdhGOj GdLOjO(B. s (2020)
(3GSJgOa gPG GdHMK HUaI QFjSjI cdG ef GdJYQa Ydj CfeGW GdJYGbH GdeMUhdj GdSGFOI Hjf GdRQGY GdeHMhKjf NdGd (B3 (3SfhGJ RQGYjI eJJGdjI , hJMOjO eSJhj QVG GdRQGY GdeHMhKjf Yf GfeGW GdJYGbH GdeMUhdj GdSGFO dOjge ,hGge GdeJZjQGJ GdeQJHWI Hg(B.s
(3jMJhj Ydj eQGLYs
(3edNU HGddZI GdEfLdjRjIs
Keywords: (3GdEQTGO GdRQGYjs -- (3GdhGOj GdLOjO (B((3eUQ(B)s; (3GdOhQI GdRQGYjIs -- (3GdhGOj GdLOjO (B((3eUQ(B)s